JURNAL REVIEW: KONDISI VBNC (viable but nonculturable) PADA BAKTERI PATOGEN PANGAN GRAM NEGATIF - Yesica Marcelina Romauli Sinaga; Ratih Dewanti-Hariyadi; Firman Fajar Perdhana; Tri Isti Rahayu (The Journal of Teknologi Pangan, 2023)
Foodborne pathogens bacteria may enter a nongrowing state under unfavorable conditions for their growth, such as low nutrient, low pH, and low temperature. One of the nongrowing states of bacteria is a viable but nonculturable (VBNC) state. Bacteria in this VBNC condition can not form colony on agar medium daily used for enumeration of bacteria, despite, these bacteria still have viability (cellular integrity), and able to do metabolic activity like the ability to express protein, to respirate, and to do intracellular enzymatic activity. Under the VBNC state, bacteria especially the pathogens which are present in food will raise a health risk. This is worrying, because the culture method used to control food safety is thought unable to detect foodborne pathogens that are in VBNC state. Estimation of the number of pathogenic bacteria in food that is lower than the actual number, and the failure to identify foodborne pathogenic bacteria in food samples when cultured in agar plates, raise health concerns, if the food is consumed. Therefore, the presence of VBNC state in foodborne pathogenic bacteria needs to be studied further.